Effectiveness of Android-Based Mobile Learning (M-Learning) on Molecular Shape Sub-Materials to Improve Students' Visual-Spatial Intelligence - Tito Vanzal; Kusumawati Dwiningsih (Jurnal Penelitian Pendidikan IPA, 2023)
The factor causing students difficulties in understanding the shape of molecules is that students need to imagine the 3D structure of a molecule with images in 2D, so a visualization tool specifically designed to overcome problems related to this is needed. This study aims to determine the Effectiveness of Android-based M-Learning in the molecular shape sub-material to improve students' visual-spatial intelligence. This study used the 4D development model proposed by Thiagarajan (Define, Design, Develop, and Disseminate) modified by Ibrahim so that it was only carried out until the development stage. The trial of M-Learning using a One-group pretest-posttest design. The subject in this research is class IX F-3 with a number of 27 students. The effectiveness of Android-based M-Learning in terms of the increase in student learning outcomes as measured by the value of the molecular shape pretest-posttest which contains 10 multiple choice questions related to the molecular shape sub-material and visual-spatial pretest-posttest which contains 6 multiple choice questions related to spatial-visual intelligence. Research results show the molecular shape test and visual-spatial, each obtained an N-Gain of 0.63 – 1 with moderate and high feature scores. which is effective in terms of increasing student learning outcomes